“A Lot Happens After Best Supportive Care”—Unbottling the Countertransference of Health-Related Suffering in a Community Cancer Palliative Care Setting: A Qualitative Case Study - Viswanath, Vidya; Pranai, Ravuru Vamsi; Fernandes, Dolorosa; Alapati, Neeharika; Sirisha, Ketireddi; Karim, Alisha; Thakur, Priyanshu; Ram, Samanasi Chaitanya; Khan, Aaliya; Bhavani, Geddam; Shit, Suroj; Kumari, Duvvada Santha; Miriyala, Ravi Teja (Indian Journal of Medical and Paediatric Oncology, 2025)
The Integrated Hospital-based Continuity of Care project at a government tertiary cancer hospital in the department of palliative medicine aimed to relieve serious health-related suffering and facilitate care along the continuum through home visits by a multidisciplinary team to patients on best supportive care. These patients transitioning through palliative care engender reciprocal feelings of suffering among the team members, impacting their well-being.Countertransference includes the conscious and unconscious feelings experienced by the health care provider toward the patient. Accepted as appropriate and unavoidable, it is important to understand, recognize, and address the issues related to countertransference of health-related suffering. Following a debriefing session, the feelings documented by a downcast nurse, as a doodle, depicting the abandonment of a patient from her own home, formed the background for this study.This study aimed to explore the experiences of the palliative care team caring for patients with cervical cancer in the home care setting.This qualitative case study method included the multidisciplinary team in the department of palliative medicine as participants. There were multiple sources of data like four sketches with captions depicting patients with cervical cancer at home drawn by the doctor and its interpretation by the team, reflective journaling notes, and transcripts from the focus group discussion. Following data familiarization and analysis, themes were derived.The first theme described the dejection felt by the participants as they witnessed patients with disfigurement, stigma, and neglect. These memories lingered and the second theme dealt with their deliberations as they navigated through self-doubt. The realization that home care is an invaluable experience was the third theme. The reflection that “every struggle is unique” and how art could help in training, learning, and catharsis was the fourth theme.The results of our study resonate with the dual process model of grief; moving from the loss-oriented response as they witnessed suffering in patient's homes toward the restoration-oriented response where they felt gratitude and acknowledged the value of caring for the person at home. Art was the ice breaker in enabling this reflection.
Keywords: countertransference; home care services; palliative care; continuity of patient care; grief